Karakteristik Pengujian Tegangan Tembus Arus Bolak Balik Pada Minyak Kelapa (Cocos Nucifera) Sebagai Alternatif Isolasi Cair - Rizal, Ghane Sha; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research is looking for the ratio of breakdown voltage between mineral oil and Cocos nucifera oil as an alternative of liquid insulation. The test of oil uses half-spare electrode. The results of the research, the value of oil breakdown voltage Cocos Nucifera after reduced water content is higher than mineral oil. This research also examined varies gap space, water content and varies in temperature rise on Cocos Nucifera oil to determine the effect of breakdown voltage. Less water level in oil is higher value of breakdown voltage. To be used as an alternative to liquid insulation, it must meet several criteria according to the standared spesifications of liquid insulation oil. Cocos Nucifera oil before reducing in water content has refer several requirements including density and viscosity based on standard SPLN 49-1:1982. Cocos nucifera oil after reducing in water content has met several criteria requirements including breakdown voltage, density, and viscosity. While for the specifications of the pour point and flash point not saturate the criteria as an alternative to liquid insulation. Keywords: Liquid insulation,breakdown voltage, cocos nucifera oil.